2002
DOI: 10.1046/j.1469-8137.2002.00326.x
|View full text |Cite
|
Sign up to set email alerts
|

A role for the cuticular waxes in the environmental control of stomatal development

Abstract: SummaryThe mechanism of guard cell development is currently attracting much interest. The recent use of Arabidopsis mutant plants has shed new light on the pathways that regulate the development and patterning of specialized cells such as guard cells, trichomes and roots hairs within the plant epidermis. Here, we review this literature focusing on the insights provided into guard cell development. We also discuss our current knowledge of how environmental variables may impact on guard cell development and, in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 28 publications
0
23
0
3
Order By: Relevance
“…Although observations from a wide range of species indicate that the average stomatal response is a reduction in density with increasing [CO 2 ], there is nevertheless, considerable variation from large reductions, to no change, to large increases in density (Ferris and Taylor 1994;Ceulemans et al 1995;Woodward and Kelly 1995;Royer 2001;Woodward et al 2002). Current evidence suggests that the regulation of stomatal development in response to environmental change is mechanistically different from those cell-to-cell mechanisms that determine stomatal number and placement by species (Holroyd et al 2002) and is a genetic response Hetherington and Woodward 2003) with the HIC gene identified as a regulator of stomatal numbers. This is an interesting observation since no decrease in stomatal density was found in mature leaves of any individual species at three sites where both woody and herbaceous species were measured after 4 years in FACE (Reid et al 2003) and reductions have rarely been identified in field-grown trees (Norby et al 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Although observations from a wide range of species indicate that the average stomatal response is a reduction in density with increasing [CO 2 ], there is nevertheless, considerable variation from large reductions, to no change, to large increases in density (Ferris and Taylor 1994;Ceulemans et al 1995;Woodward and Kelly 1995;Royer 2001;Woodward et al 2002). Current evidence suggests that the regulation of stomatal development in response to environmental change is mechanistically different from those cell-to-cell mechanisms that determine stomatal number and placement by species (Holroyd et al 2002) and is a genetic response Hetherington and Woodward 2003) with the HIC gene identified as a regulator of stomatal numbers. This is an interesting observation since no decrease in stomatal density was found in mature leaves of any individual species at three sites where both woody and herbaceous species were measured after 4 years in FACE (Reid et al 2003) and reductions have rarely been identified in field-grown trees (Norby et al 1999).…”
Section: Introductionmentioning
confidence: 99%
“…The similarities between the stomatal reconstruction of paleo-[CO 2 ] and plant photosynthesis and stress physiology derived from epidermal cell density suggest that either abaxial stomatal formation and adaxial epidermal cell development are genetically and developmentally linked (Holroyd et al, 2002) and/or that reduced convective heat loss via transpiration is one of the primary hypothesized causes of plant stress across the TJB (McElwain et al, 1999). The stomatal reconstruction of paleo- [CO 2 ] is based on stomata of Ginkgoales and Stenopteris specimens collected by Thomas Harris during the 1920s from TJB sections in East Greenland compiled into a composite stratigraphy (Harris, 1937), while those specimens analyzed in this study were collected in 2002 from a single site in East Greenland (McElwain et al, 2007).…”
mentioning
confidence: 99%
“…Consistent with the role of HIC in epicuticular wax biosynthesis, mutations in two additional epicuticular wax biosynthesis genes, CER1 and CER6, confer significant increases in stomatal density even in the ambient CO 2 levels Holroyd et al 2002). Unlike HIC, CER1 and CER6 affect wax composition in the entire epidermis, including pavement cells (Aarts et al 1995;Fiebig et al 2000).…”
Section: Environmental Control Of Stomatal Patterningmentioning
confidence: 68%